2012
DOI: 10.1007/s10762-012-9925-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Microwave Properties of Silica Xerogel Glass-Ceramic Sintered by Sub-millimeter Wave Heating using a Gyrotron

Abstract: In this paper, we present and discuss experimental results from a microwave sintering of silica glass-ceramics, produced from amorphous silica xerogel extracted from sago waste ash. As a radiation source for a microwave heating a sub-millimeter wave gyrotron (Gyrotron FU CW I) with an output frequency of 300 GHz has been used. The powders of the amorphous silica xerogel have been dry pressed and then sintered at temperatures ranging from 300°C to 1200°C. Microwave absorbing properties of the sintered samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Therefore, SiO 2 production from these sources on an industrial scale is not technologically or economically viable. In our study, SiO 2 in the form of silica xerogel was prepared using a sago waste ash (Aripin et al, 2011;Aripin et al, 2012) as a starting powder and was used to produce TiO 2 -SiO 2 composites by mixing 20 wt% and 40 wt% of TiO 2 into SiO 2 . It was found that, at 900°C, the size of the anatase crystallites are 26.3 nm and 21.4 nm for 20 wt% and 40 wt% of TiO 2 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SiO 2 production from these sources on an industrial scale is not technologically or economically viable. In our study, SiO 2 in the form of silica xerogel was prepared using a sago waste ash (Aripin et al, 2011;Aripin et al, 2012) as a starting powder and was used to produce TiO 2 -SiO 2 composites by mixing 20 wt% and 40 wt% of TiO 2 into SiO 2 . It was found that, at 900°C, the size of the anatase crystallites are 26.3 nm and 21.4 nm for 20 wt% and 40 wt% of TiO 2 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics make it possible to become a good alternative candidate of microwave absorbing material. The study of this material for microwave absorber as well as alumina as ceramic materials are performed by our group research [7][8][9][10][11][12][13]. The silica was extracted from various agricultural wastes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a very high frequency microwave processing system within a range of sub-millimeter waves with a frequency of 300 GHz has been developed at FIR Center [4]. This device has been successfully used for sintering alumina, zirconia, and silica [5][6][7][8]. Researchers believe that the use of higher frequencies possesses greater microwave effects and the existing problems found in lower frequencies would be more easily solved.…”
Section: Introductionmentioning
confidence: 99%
“…Those enhancements are grouped into two. The first enhancement consists of indirect evidence of diffusion such as observations of enhanced sintering, grain growth, or reaction zones [3,[5][6][7][8][9][10]. This type of observations does not provide clear evidence of enhanced diffusion due to its difficult in interpretation for complex processes such as sintering, grain growth, phase change, and chemical reaction.…”
Section: Introductionmentioning
confidence: 99%